2022
DOI: 10.1101/2022.06.04.22275962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of gene fusions associated with amyotrophic lateral sclerosis

Abstract: Genetics is an import risk factor for amyotrophic lateral sclerosis (ALS), a devastating neurodegenerative disease affecting motor neurons. Recent findings demonstrate that, in addition to specific genetic mutations, structural variants caused by genetic instability can also play a causative role in ALS. Genomic instability can lead to deletions, duplications, insertions, inversions, and translocations in the genome, and these changes can sometimes lead to fusion of distinct genes into a single transcript. Wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…ADAMTSL3-SH3GL3 , reported recently 20, 37 , was an inversion of SH3GL3-ADAMTSL3 38 on 15q25, encoding thirteen isoforms and coded for 42 alternatively-spliced isoforms (Fig.3). Its ADAMTSL3-SH3GL3 main isoform a was expressed only at 19% of the KANSARL (KANASL1-ARL17A) main isoform level and encoded a conceptual 202 aa ADAMTSL3-SH3GL3 fusion protein over two-thirds of which was from SH3GL3 .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…ADAMTSL3-SH3GL3 , reported recently 20, 37 , was an inversion of SH3GL3-ADAMTSL3 38 on 15q25, encoding thirteen isoforms and coded for 42 alternatively-spliced isoforms (Fig.3). Its ADAMTSL3-SH3GL3 main isoform a was expressed only at 19% of the KANSARL (KANASL1-ARL17A) main isoform level and encoded a conceptual 202 aa ADAMTSL3-SH3GL3 fusion protein over two-thirds of which was from SH3GL3 .…”
Section: Resultsmentioning
confidence: 93%
“…Table 3 showed that SH3GL3-ADAMTSL3 was almost ubiquitously expressed in ASL, OND, AD, MTLE, and two controls. In comparison, it was detected in 7.5% of 133 GTEx brain cortexes and suggested that SH3GL3-ADAMTSL3 38 and ADAMTSL3-SH3GL3 20, 37 behaved similarly. Since SH3GL3-ADAMTSL3 EFG can be treated as a permanent HFG with a recurrent frequency of 100%, we speculated that ADAMTSL3-SH3GL3 had a much higher recurrent frequency than 1.5% of GTEx brain cortexes and was activated to be expressed by interactions between genetic and environmental lesions during aging.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gene fusion usually involves deletion, insertion, translocation, inversion, or read-through transcription of adjacent genes [ 40 ]. Recently, several fusion genes have been identified from RNA-Seq data of ALS patients, including TVP23C–CDRT4, AC090517.5–ZNF280D, MAILR–ATP6V1C1 and C8orf44–SGK3 by neighbor fusion as well as YAF2–RYBP by inter-chromosomal fusion [ 41 ]. Based on the results of this study, the fusion of DCTN1-KIF5A requires further investigation.…”
Section: Discussionmentioning
confidence: 99%